C4b Binding Protein Acts as an Innate Immune Effector Against Influenza A Virus - Varghese, Praveen M.; Murugaiah, Valarmathy; Beirag, Nazar; Temperton, Nigel; Khan, Haseeb A.; Alrokayan, Salman H.; Al-Ahdal, Mohammed N.; Nal, Beatrice; Al-Mohanna, Futwan A.; Sim, Robert B.; Kishore, Uday (Frontiers in Immunology, 2021)
C4b Binding Protein (C4BP) is a major fluid phase inhibitor of the classical and lectin pathways of the complement system. Complement inhibition is achieved by binding to and restricting the role of activated complement component C4b. C4BP functions as a co-factor to factor I in proteolytic inactivation of both soluble and cell-bound C4b, thus restricting the formation of the lectin pathway C3-convertase, C4b2a. C4BP also accelerates the natural decay/dissociation of the C3 convertase. This makes C4BP a prime target for exploitation by pathogens to escape complement attack as seen in Streptococcus pyogenes or Flavivirus. Here, we wanted to examine whether C4BP can act on its own in a complement independent manner, against pathogens. We demonstrate that C4BP binds H1N1 and H3N2 subtypes of Influenza A Virus (IAV) most likely via multiple sites in Complement Control Protein (CCP) 1-2, 4-5 and 7-8 domains of its α-chain. In addition, our study suggests that C4BP CCP1-2 binds H3N2 better than H1N1. C4BP bound three IAV envelope proteins Haemagglutinin (~70 kDa), Neuraminidase (~55 kDa), and Matrix protein 1 (~25kDa). C4BP suppressed H1N1 subtype infection into the lung epithelial cell line, A549, while it promoted infection by H3N2 subtype. C4BP restricted viral entry for H1N1but had the opposite effect for H3N2, as evident from experiments using pseudo-typed viral particles. C4BP downregulated mRNA levels of pro-inflammatory IFN-α, IL-12, and NFκB in the case of H1N1, while it promoted a pro-inflammatory immune response by upregulating IFN- α, TNF-α, RANTES and IL-6 in the case of H3N2. We conclude that C4BP differentially modulates the efficacy of Influenza A virus entry and hence, replication in a target cell in a strain-dependent manner, and acts as an entry inhibitor for H1N1. Thus, CCP containing complement proteins such as factor H and C4BP may have additional defence roles against IAV that do not rely on the regulation of complement activation.